Bifunctional acid-base strontium-titanium mixed oxides supported on SBA-15 for selective synthesis of renewable branched bio-jet fuel precursor - Meemanah, Thanatchai; Chotirattanachote, Atikhun; Ahmad, Junaid; Rashid, Umer; Ngamcharussrivichai, Chawalit (Elsevier, 2023)
Herein, furfural, which is a lignocellulose-derived platform chemical, was converted into a bio-jet fuel precursor via aldol condensation with 2-butanone using strontium (Sr) and titanium (Ti) mixed oxides (STO) loaded onto mesoporous silica SBA-15 (SBA15). A series of acidobasic STO/SBA15 catalysts were prepared via incipient wetness impregnation by systematically varying the mixed oxide loading and Sr:Ti molar ratio of the catalysts. The STO/SBA15 catalysts exhibited a well-mesostructured order, high dispersion of metal oxides, and good textural properties. The acidic and basic properties of the catalysts were facilely controlled by varying the metal oxide composition and amount of STO loaded onto the SBA15 support. The aldol condensation was carried out batchwise under a pressurized nitrogen atmosphere. The products formed in the reaction comprised 9“18 carbon atoms. The yield and selectivity of ±,²-unsaturated C9 ketone with branched molecular structure (C9B) were strongly influenced by the acid“base properties of the catalyst and the reaction conditions. 20STO(2:1)/SBA15 was the suitable catalyst, realizing > 99 furfural conversion and 78.3 C9B yield under the following optimized conditions: 4 wt catalyst loading, 1:5 furfural:2-butanone molar ratio, 180 °C reaction temperature, and 5 h reaction time.